The Role of B Cells in Carriage and Clearance of Mycoplasma pneumoniae From the Respiratory Tract of Mice. (1st November 2017) - Meyer Sauteur, Patrick M; de Groot, Ruben C A; Estevão, Silvia C; Hoogenboezem, Theo; de Bruijn, Adrianus C J M; Sluijter, Marcel; de Bruijn, Marjolein J W; De Kleer, Ismé M; van Haperen, Rien; van den Brand, Judith M A; Bogaert, Debby; Fraaij, Pieter L A; et al.
Abstract : Mycoplasma pneumoniae ( Mp ) is carried in the upper respiratory tract (URT) of mice after symptomatic infection. B cells and Mp -specific antibodies are crucial for Mp clearance in the lungs of mice but are limited in clearing Mp from the URT. Abstract: Background: Carriage of Mycoplasma pneumoniae ( Mp ) in the nasopharynx is considered a prerequisite for pulmonary infection. It is interesting to note that Mp carriage is also detected after infection. Although B cells are known to be involved in pulmonary Mp clearance, their role in Mp carriage is unknown. Methods: In this study, we show in a mouse model that Mp persists in the nose after pulmonary infection, similar to humans. Results: Infection of mice enhanced Mp -specific immunoglobulin (Ig) M and IgG levels in serum and bronchoalveolar lavage fluid. However, nasal washes only contained elevated Mp -specific IgA. These differences in Ig compartmentalization correlated with differences in Mp -specific B cell responses between nose- and lung-draining lymphoid tissues. Moreover, transferred Mp -specific serum Igs had no effect on nasal carriage in B cell-deficient μMT mice, whereas this enabled μMT mice to clear pulmonary Mp infection. Conclusions: We report the first evidence that humoral immunity is limited in clearing Mp from the upper respiratory tract.